New-Generation Social and Political Ideas in the 2023 Phan Waen Fah Award–Winning Short Stories - Naijarun, Khwanchanok (Archīum Ateneo, 2024)
This research is aimed at analyzing the social and political ideas of new-generation characters (i.e., teenagers, young adults, university students) in the short stories that won the Phan Waen Fah Literature Prize in 2023. The study employs a qualitative methodology to understand and interpret the ten out of thirteen prize-winning short stories. Through textual analysis, the study identifies two main concepts explored in the narratives, namely, liberal democracy, which includes freedom of sexuality and freedom of speech, and moral politics, which encompasses respecting elders, being a good person under a democratic regime, fostering unity, and being wise about using technology. These ideas are primarily conveyed through the short stories’ plot, theme, setting, and characters.